The Existence of Penal Mediation in the Perspective of Indonesian Criminal Law Reform - Ghufron Kamatsala Ghafarulloh (UNIVERSITAS PAKUAN, 2026)
The law has long been viewed as a rigid set of norms that is overly focused on the formal legal system; this situation, in turn, has given rise to various complexities and conflicts in the social life of the community. In order to bridge the gap between the law which has traditionally been formal and inflexible and the real-life conditions within Indonesian society, one approach that can be taken is to provide space for mechanisms to resolve criminal cases outside of court, known as Penal Mediation. This study aims to examine and discuss the status and relevance of Penal Mediation as an alternative pathway in the handling of criminal cases, particularly from the perspective of criminal law reform in Indonesia. The method used in this study is normative legal research based on a literature review. The findings of this study reveal that the implementation of Article 132(1)(g) of Law No. 1 of 2023 on the Criminal Code further strengthens the legitimacy of resolving criminal cases through non-litigation channels. This marks a significant milestone, given that previously, regulations regarding such mechanisms were scattered across various sectors and lacked comprehensiveness within the existing regulations and internal policies of law enforcement agencies in Indonesia.